Animals and Artists: An Exploration of Impossible Encounters - Atkinson, Elizabeth Eleanor Jacqueline (Intellect Books, 2022)
Animals and Artists discusses a selection of modern and contemporary artworks that challenge traditional representations of nonhuman animals, and that expose human viewers to animal otherness. It argues that the individuated and discrete human self in possession of consciousness, rationality, empathy, a voice, and a face, is open to challenge by nonhuman capacities such as distributed cognition, gender ambiguity, metamorphosis, mimicry and avian speech. In traditional philosophy, animals represent all that is lacking in humankind. However, Animals and Artists argues that just because humans frame 'the animal' as a negative term, their binary opposite and everything that they are not, does not mean that animals have no meaning in themselves. Rather, animals in their very unknowability, mark the limits of human thinking. By combining art analysis with poststructuralist, post humanist and animal studies theories as well as scientific research, Elizabeth decentres the human and establishes a new position where differences are embraced. In our current moment of ecological crisis, Animals and Artists brings readers into solidarity with other animal species, among them spiders, silkworms, bees, parrots and octopuses. The book raises empathy for other live forms, drawing attention to the shared vulnerabilities of human and nonhuman animals, and in so doing underlines the power of art to bring about social change. Readers will include animal studies scholars, artists, art historians, Jean Painlevé scholars, Surrealist enthusiasts, non-academics who are concerned about the human-animal relationship, the environment or larger identity politics issues.